The independence character of elementary school children with autism: A case study - Ari Setiawan; Syarief Fajaruddin; Nuryani Dwi Astuti; Devi Wahyu Ertanti; Sri Budyartati; Jamilah Jamilah; Machmudah Machmudah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2025)
This case study explores the development of independence in an elementary school-aged child with Autism Spectrum Disorder (ASD). Using qualitative methods—including direct observation, semi-structured interviews, and document analysis—the study identified key factors that facilitated independent behavior in both home and school settings. The child demonstrated increased autonomy in daily tasks such as toileting, dressing, and class participation, particularly when supported by structured interventions including visual schedules, task analysis, and token reinforcement systems. A significant finding was the role of consistent collaboration between parents and teachers, which enabled the child to generalize skills across environments. These results affirm the importance of individualized support strategies and inter-setting consistency in promoting independence among children with ASD. The study concludes by recommending sustained, context-sensitive interventions and further research across multiple participants and settings to inform evidence-based practices in special education.